PREPARATION AND ANALYSIS OF LYOPHILIZED DOSAGE FORM LHS-1208 BY THIN CHROMATOGRAPHY AND A SPECTROPHOTOMETERY - I. D. Gulyakin; L. L. Nikolaeva; M. V. Dmitrieva; O. L. Orlova; A. P. Polozkova; N. A. Oborotova; E. V. Ignatieva; N. A. Dmitricheva; I. V. Yartseva; Z. S. Shprakh (Разработка и регистрация лекарственных средств, 2019)
The work is dedicated to the development of technology for obtaining a freeze-dried dosage form LHS-1208 and the establishment of methods of quality control of the drug. The authors have shown spectrophotometric analysis techniques and flash chromatography.